Lack of efficacy of ergocalciferol repletion - Thomas Wasser; Richard Alweis; Jorge Scheirer; Corey Ephrussi; Meredith Lamanna; Amal Kebede (Greater Baltimore Medical Center, 2012)
Introduction: Vitamin D has become an area of intensive scrutiny, both in medical and lay literature. However, there are limited data to suggest proper repletion regimens for those patients who have hypovitaminosis D. Consequently, various methods are used in clinical practice. The aim of this study was to assess the efficacy of various treatment strategies for hypovitaminosis D in an ambulatory internal medicine practice. Methods: A retrospective chart review between October 2005 and June 2010 of a suburban internal medicine practice was performed via query of the electronic medical record (Centricity, General Electric Healthcare, UK). Patients with a 25-hydroxyvitamin D concentration less than 32 mg/dl were identified and treated. Treatment success was defined as 25-hydroxyvitamin D concentrations greater than 32 mg/dl. Statistical analysis to assess changes in vitamin D level controlling for season, comorbidities, and demographics were used. Results: A total of 607 treatment episodes were identified, with 395 excluded due to lack of follow-up vitamin D level within 16 weeks, no treatment documented, topical treatment, doxercalciferol treatment, or non-compliance. Of the remaining patients, there were 212 treatment instances on 178 patients. Ergocalciferol 50,000 international units (IU) was used most frequently (71.4% of the time.). A higher initial vitamin D level was positively associated with treatment success (adjusted odds ratio = 1.11, p=0.002). Increased doses of ergocalciferol increased the likelihood of treatment success (p=0.0011). Seasonal variation was related to posttreatment 25-hydroxyvitamin D concentration as was body mass index (BMI) (p=0.003 and p=0.044). Conclusion: Pretreatment levels of 25-hydroxyvitamin D, BMI, season, and vitamin D dose are predictors of successful hypovitaminosis D treatment. Our data suggest that patients with initial 25-hydroxyvitamin D concentrations of <20 should be treated with a higher total dose of ergocalciferol than 50,000 IU for 8 weeks. Further studies, including prospective, randomized trials, are needed to determine an optimal treatment protocol to account for the numerous variables.